(untitled) (Academic Journal of Internal Affairs, 2021)
In recent years, one of the government’s key strategic objectives has been to recruit adequate staff for the civil service and to employ well-prepared, committed and dedicated staff. For this it is necessary to know exactly organizational expectations regarding the entrants and to define the competence requirements. In our study, we present the partial results of an empirical research (KÖFOP 2.1.5. project) on the basic expectations of public service organizations in relation to new entrants. In the research we used an interview and questionnaire method. The results show that organizations expect compliance, effective work, and psychological resilience from career starters. It also turned out that there are significant differences between the competence requirements of law enforcement, central administration and local government in several cases. It should be emphasized that, the actual level of competence of career starters almost always falls short of organizational expectations. Our results show that public administration and law enforcement organizations must pay special attention to the definition and development of competencies, their application in the selection of the workforce, and the operation of competency management. Emphasizing also that the mismatch between organizational expectations and the needs of the younger generation hinders the integration and retention of the workforce and raises the issue of career management, generational change and the competitiveness of the civil service.